PENINGKATAN KAPABILITAS AUDITOR INTERN UNTUK MENDUKUNG AKUNTABILITAS ANGGARAN PERTAHANAN - Raharjo, Budi; Sarjito, Aris; Duarte, Editha Praditya (Gapenas Publisher, 2024)
The government as a state organizer has a responsibility for the budget it manages. Accountable defense budget management is a form of public accountability that is the duty and function of the Ministry of Defense. The Inspectorate General of the Ministry of Defense as a Government Internal Supervisory Apparatus (APIP) has a strategic role in improving government governance, including a role in supporting the accountability of defense budget management. To carry out this role, adequate auditor capability is required. This study aims to understand the efforts to improve the capabilities of the auditors of the Inspectorate General of the Ministry of Defense to support the accountability of defense budget management. Qualitative method was used in this research with descriptive analysis approach. Data collection was carried out by interview method based on the Internal Audit Capability Model (IACM). The results showed that there have been efforts to increase the capability of the auditors of the Inspectorate General of the Ministry of Defense to level 3 (delivered), but the achievement of defense budget accountability shown through the Government Agency Performance Accountability System (SAKIP) still requires continuous improvement.